2011
DOI: 10.1179/026708309x12506934374047
|View full text |Cite
|
Sign up to set email alerts
|

Sound absorption of open celled aluminium foam fabricated by investment casting method

Abstract: The sound absorption behaviour of an open celled aluminium foam fabricated by investment casting method was examined and correlated with the pore size, sample thickness and backing air gap depth in the present study. The foam shows low sound absorption coefficients at relatively low frequencies or with relatively thin sample thickness due to its 90% or higher open porosity. As frequency or sample thickness increases, the sound absorption is significantly enhanced. Furthermore, if the sample is backed with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Therefore, it is concluded that relatively small pores of the foams are beneficial to sound absorption. This tendency is consistent with those observed in aluminum foams [4,5,6]. …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, it is concluded that relatively small pores of the foams are beneficial to sound absorption. This tendency is consistent with those observed in aluminum foams [4,5,6]. …”
Section: Resultssupporting
confidence: 92%
“…As mentioned above, two mechanisms are responsible for the sound absorption characteristics of Al foams, i.e. , the viscous losses resulting from the air flow and the thermal losses originating from the friction between the air and the cell wall through the vibration of air in the pores [4,5,6,9]. It can be found after the PEO treatment that there are small pores at micrometer level distributed in the surface of the aluminum foams.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The porosity and the average pore diameter are 92% and 1.0 mm, respectively. The detailed process and the cell characterization can be seen in reference [3]. Hydrothermal method was utilized to synthesize ZnO micro-rods on the cell surface of Al foam in the following steps: (1) soaking the Al foam samples with the size of f29 Â 30 mm in a solution of 0.015 mol/L zinc acetate dehydrate in ethanol for 1 min; (2) taking out the soaked Al foam samples from the solution and drying them with a hand electric dryer;…”
Section: Synthesis Of Zno Micro-rodsmentioning
confidence: 99%